Lupus mastitis as a first manifestation of systemic disease: About two cases with a review of the literature. Issue 92 (July 2017) - Voizard, Béatrice; Lalonde, Lucie; Sanchez, Lilia Maria; Richard-Chesnay, Johanne; David, Julie; Labelle, Maude; El Khoury, Mona; Trop, Isabelle
Highlights: Lupus mastitis can be the first manifestation of SLE in patients not previously diagnosed with this condition. Lupus mastitis manifests clinically as subcutaneous masses or nodules, with or without cutaneous involvement. Radiological manifestation of lupus mastitis are non-specific findings that require biopsy for diagnosis. Lupus mastitis may mimic inflammatory carcinoma. Biopsy is required to eliminate underlying cancer. Fat necrosis and coarse calcifications may be seen in more chronic lupus mastitis. Abstract: Lupus mastitis is an uncommon manifestation of systemic lupus erythematosus (SLE) that affects the subcutaneous fat in the breast, much like lupus panniculitis, but additionally involves the mammary gland. We report on two women for whom lupus mastitis was the initial manifestation of SLE and provide a literature review of 34 additional cases reported in the Anglo-Saxon and French literature since 1971, making this the largest review to date. Lupus mastitis (LM) can manifest clinically as subcutaneous masses that may be painful, or may present cutaneous involvement such as thickening and discolouration. The radiologic manifestations of LM are broad and include calcifications, masses and asymmetries. Most often, excluding malignancy requires percutaneous biopsy, with histologic findings that are virtually pathognomonic for SLE. Thus, surgery is avoided and medical management can begin, antimalarial drugs and corticosteroids in most cases.